A Prospect and Challenges for Adopting Constitutional Complaint and Constitutional Question in the Indonesian Constitutional Court - Pan Mohamad Faiz (The Constitutional Court of the Republic of Indonesia, 2016)
A jurisdiction of the Indonesian Constitutional Court concerning constitutional adjudication is only limited to review the constitutionality of national law. There is no mechanism for challenging any decision or action made by public authorities that violate fundamental rights enshrined in the Indonesian Constitution. This article argues that constitutional complaint and constitutional question might be adopted as new jurisdictions of the Indonesian Constitutional Court in order to strengthen the protection of fundamental rights of its citizen. It also identifies main problems that will be faced by the Constitutional Court in exercising constitutional complaint and constitutional question. For instance, the Court will be burdened with too many cases as experienced by other countries. A clear mechanism for filtering applications lodged to the Constitutional Court and the time limit for deciding cases are important elements that have to be regulated to overcome the problems. In addition, the institutional structure of the Constitutional Court has to be improved, particularly to support its decision- making process.